Analysis of Magneto-Mechanical Response for Magnetization-Graded Ferromagnetic Material in Magnetoelectric Laminate - Zhou, Hai (Materials (Basel), 2020)
This paper analyzes the dynamic magneto-mechanical response in magnetization-graded ferromagnetic materials (MGFM) comprised of high-permeability Finemet and traditional magnetostrictive materials. The theoretical modeling of the piezomagnetic coefficient that depends on the bias magnetic field of MGFM is proposed by using the nonlinear constitutive model of a piezomagnetic material, the magnetoelectric equivalent circuit method, and the simulation software Ansoft. The theoretical variation of piezomagnetic coefficients of MGFM on the bias magnetic field is in good agreement with the experiment. Using the piezomagnetic coefficient in the magnetoelectric voltage model, the theoretical longitudinal resonant magnetoelectric voltage coefficients have also been calculated, which are consistent with the experimental values. This theoretical analysis is beneficial to comprehensively understand the self-biased piezomagnetic response of MGFM, and to design magnetoelectric devices with MGFM.